Validade do questionário perfil de atividade humana para estimar a aptidão cardiorrespiratória e a capacidade de exercício de indivíduos pós-acidente vascular encefálico na fase crônica - Sherindan Ayessa Ferreira de Brito (2020)
The stroke is a leading cause of disability worldwide. The reduction in cardiorespiratory fitness and exercise capacity are impairments commonly found in these individuals. The Cardiopulmonary Exercise Testing (CPET) is the gold standard for the assessment of the cardiorespiratory fitness expressed by peak oxygen uptake (VO2peak). However, the CPET requires complex and expensive equipment. Submaximal field exercise tests, such as the 6-minute Walking Test (6MWT) and the Incremental Shuttle Walking Test (ISWT) are commonly used to assess exercise capacity. To perform these tests, 30- and 10-meter hallways are required, respectively. In addition, the individuals must be able to walk at an adequate speed to follow the ISWT audio signal. These factors reduce clinical applicability of these tests. The Human Activity Profile (HAP) questionnaire, a simple, easily administrated and no cost instrument, allows estimating the VO2peak (mL.kg-1.min-1) through the lifestyle energy consumption (LEC). In addition, the HAP provides the maximum activity score (MAS) and the adjusted activity score (AAS), commonly used to assess the physical activity level. However, the validity of the HAP for the assessment of these outcomes in individuals after stroke has not yet been investigated. Thus, the objectives of this study were: a) to investigate the concurrent validity of the HAP to estimate the cardiorespiratory fitness and b) to investigate the construct validity of the HAP to asses the exercise capacity in individuals after stroke. Fifty-seven individuals with stroke (54 ± 11 years of age) were included. On the first day of evaluation, the HAP was administered and the 6MWT and the ISWT were performed in randomized order. On the second day the CPET was performed. Intraclass Correlation Coefficient (ICC) was used to evaluate the agreement between the VO2peak (mL.kg-1.min-1) estimated by the HAP and the VO2peak (mL.kg-1.min-1) measured by the CPET (concurrent validity). Spearman correlation was used to investigate the correlation between the HAP scores (LEC, the MAS and the AAS, in points) and the distance walked (in meters) in the 6MWT and the ISWT (construct validity) (α=0.05). Significant and high magnitude agreement was found between the VO2peak estimated by the LEC (HAP) and the VO2peak obtained through the CPET (CCI=0.75). Significant and low to moderate magnitude correlations were found between the HAP scores (LEC, MAS and AAS) and the distance walked in the 6MWT/ISWT (0.46≤rho≤0.62; 0.34≤rho≤0.58, respectively). The HAP demonstrated adequate validity to estimate cardiorespiratory fitness and to assess exercise capacity in individuals after stroke. Therefore, it can be used as an alternative method to assess these outcomes when CPET and submaximal clinical exercise tests (6MWT and ISWT) cannot be performed.